Digital Narratives and Student Identity: A Phenomenological Study of Generation Alpha in Education - Hayati, Rifaatussalwa; Murtado, Dodo (Journal of Pedagogi, 2025)
The dominance of digital technology in the lives of Generation Alpha has created fundamental changes in the way self-identity is formed, understood, and expressed. Since an early age, this generation has grown up in a digital environment filled with algorithms, social media, and online culture that is both interactive and performative. The digital narratives they consume and produce not only shape their self-representation, but also influence their cognitive, affective, and social structures. This study aims to examine in depth how digital narratives play a role in the process of identity formation of Generation Alpha students, especially in the context of education. Using a qualitative approach with a phenomenological method, this study involved junior high school students who actively use digital media as key participants. Data were collected through in-depth interviews, participant observation, and digital documentation, then analyzed using Moustakas' (1994) framework. The results of the study show that student identities develop fluidly, temporarily, and are often curated to meet social expectations in online spaces, which are not always in line with the norms of educational institutions. These findings highlight the need for adaptive, reflective, and empathetic pedagogical transformation, as well as the importance of critical digital literacy in guiding students to build authentic, healthy, and empowered identities amidst the complex challenges of the digital world